The effect of feeeding frequency on body and carcass weight of commercial broiler chickens - Ahmet Nazlıgül; H. Erbay Bardakçıoğlu (Eurasian Journal of Veterinary Sciences)
This study was earned out to determine the effect ol feeding regimes on broiler performance. Broilers were feed in three groups related with leeding frequencies. The first group was led in one time at 900 a.m. while second was fed in two times, at 900 a.m. and 1500 p.m., and third one was ted in three times, at 900 a.m., 1300 and 1700 p.m. everyday. Body weight averages were 2112.3, 2138.3 and 2208,9 g respectively tor the groups. There were nonsignificant differences among the three groups for all characteristics ol broiler performance. The second and third groups were belter than first group, except sixth week lor body weight. Carcasses have the heaviest values for the third group which was fed in three times a day, and the lowest lor lirsl group. As a conclussion more frequently feeding may increase carcass yield and productivity economicaly in broilers.